Method of manufacturing molds and molds
Patent Information
- Application Number
- JP2023127455
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0019】 本発明の樹脂成形品の製造に用いる金型、その金型の製造方法によれば、安価で経年劣化が少なく環境負荷が小さい抗菌性の樹脂成形品を製造することができる。
Smart Images

Figure 2025023387000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a mold used for producing a resin molded product and a method for producing the mold. [Background technology]
[0002] The domestic market for antibacterial products has recently reached 1 trillion yen, and a graph showing the number of products registered with the SIAA mark for antibacterial / anti-fungal properties by SIAA (Society of International Antibacterial Articles) shows that the number of registered products is steadily increasing. Due to the extremely high social need for antibacterial products, various attempts have been made to impart antibacterial properties to the field of air conditioners, for example.
[0003] Patent Document 1 has the objective of providing an air conditioner that makes it easy to remove dust and dirt from the filter and also suppresses the growth of bacteria from the dust, and discloses an air conditioner that includes a heat exchanger, a filter arranged upstream of the heat exchanger, and a blower fan that blows the air that has passed through the filter so that it exchanges heat in the heat exchanger, the filter comprising a metal plate on which a mesh is formed by photoetching, and an antibacterial and deodorizing resin coated with a charge transfer catalyst that is arranged downstream of the metal plate in the direction in which indoor air passes. Furthermore, Patent Document 2 aims to obtain a room air conditioner equipped with a blower fan having a coating film with excellent antifouling properties, removability of adhering water, and durability, and discloses an air conditioner in which a hydrophilic / hydrophobic water-based coating material containing first silica microparticles with an average particle size of 2 to 10 nm and fluororesin microparticles with an average particle size of 50 to 500 nm is applied to the blower fan, and further a water-repellent coating material is applied to the positive pressure surface end of the blower fan. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-19498 A [Patent Document 2] Japanese Patent Application Publication No. 2008-292069 Summary of the Invention [Problem to be solved by the invention]
[0005] As shown in Patent Documents 1 and 2, conventional methods for imparting antibacterial properties to air conditioners include, for example, coating a resin surface with an antibacterial agent containing Ag ions or kneading an antibacterial agent into a resin material. However, the method of coating the resin surface with an antibacterial agent has a problem in that the coating peels off due to deterioration over time, and the antibacterial properties are lost. Furthermore, the method of kneading an antibacterial agent into a resin material requires a large amount of antibacterial agent, which is costly, and also makes it difficult to recycle the resin into which the antibacterial agent has been kneaded, resulting in a problem of a large environmental load.
[0006] In view of the above problems in the conventional technology, the present invention aims to provide a mold for use in producing antibacterial resin molded products which is inexpensive, suffers little deterioration over time, and has a small environmental impact, and a method for producing such a mold. [Means for solving the problem]
[0007] As shown in EP Ivanova et al., Nature Communications 2013, 4, 2838 and EP Ivanova et al., Small 2012, 8, 2489-2494, the present inventors came up with the idea of the present invention by noting that nanostructures exhibit high mechanical bactericidal properties regardless of their chemical composition, specifically, that nanostructure pillars destroy bacterial cell walls and physically kill bacteria.
[0008] That is, the mold of the present invention is characterized by having a gas permeable mold surface layer laminated on a gas permeable sintered metal layer.
[0009] The gas permeable sintered metal layer may be made of at least one of a gas permeable truss layer, a gas permeable porous layer, and a gas permeable lattice layer.
[0010] Two or more of the gas permeable truss layer, the gas permeable porous layer and the gas permeable lattice layer may be continuous sintered layers.
[0011] It is preferable that the surface layer of the gas permeable mold has a recess having a depth of 500 to 1000 nm formed therein.
[0012] In this case, if the depth of the recess is less than 500 nm, it is difficult to mold the resin molded product using this mold, and the antibacterial performance of the molded resin product decreases, whereas if the depth exceeds 1000 nm, there is a possibility that the antibacterial performance of the resin molded product using this mold decreases.
[0013] It is also preferable that the center-to-center distance between adjacent recesses is 500 to 800 nm. In this case, if the center-to-center distance between the recesses is less than 500 nm, it is difficult to mold a resin molded product using this mold, and the antibacterial properties of the molded resin product are not improved, whereas if the distance exceeds 800 nm, the antibacterial properties of the resin molded product using this mold are reduced.
[0014] In addition, the manufacturing method of a mold of the present invention is characterized by comprising the steps of: forming at least two or more of a gas permeable truss layer, a gas permeable porous layer, and a gas permeable lattice layer by continuous sintering; adhering a gas permeable surface layer liquid to one of the gas permeable truss layer, the gas permeable porous layer, and the gas permeable lattice layer; placing an original plate with a fine nanostructure on the gas permeable surface layer liquid adhered to the lattice layer; a photocuring reaction step of irradiating ultraviolet light to the gas permeable surface layer liquid on which the original plate with a fine nanostructure is placed; and removing the original plate with a fine nanostructure.
[0015] The original plate with a fine nanostructure has fine projections formed on its surface, and the projections on the surface preferably have a height of 500 to 1000 nm.
[0016] In the above, if the height of the protrusions is less than 500 nm, it will be difficult to mold a resin using the resulting mold, and the antibacterial performance will decrease. Conversely, if the height exceeds 1000 nm, the antibacterial performance of the resin molded product using the resulting mold may decrease.
[0017] Also, the center-to-center distance between adjacent convex portions is preferably 500 to 800 nm. In this case, if the center-to-center distance is less than 500 nm, the molded resin product obtained using the resulting mold is difficult to mold, and no improvement in antibacterial performance is observed, whereas if the center-to-center distance exceeds 800 nm, the antibacterial performance of the molded resin product obtained using the resulting mold is decreased. [Effect]
[0018] Figure 23 shows the published test results showing the viable bacteria rate versus pillar height for samples created by creating a nanostructure on a silicon substrate, setting the nanopillar pitch and width to 200 nm and 150 nm, respectively, and varying only the height, and performing antibacterial evaluation in accordance with the JIS-Z2801 film adhesion method. As shown in the figure, there is a tendency for the antibacterial rate to increase as the nanopillars become taller, and it can be seen that a pillar height of approximately 200 nm or more is necessary to exhibit antibacterial properties. It is believed that when the nanopillars are low in height, there is less damage to the cell membrane and antibacterial properties decrease, while when the pillars are taller, the number of bacteria that cause membrane damage increases. Effect of the Invention
[0019] According to the mold used for producing the resin molded article of the present invention and the method for producing the mold, it is possible to produce antibacterial resin molded articles that are inexpensive, have little deterioration over time, and have a small environmental impact. [Brief description of the drawings]
[0020] [Figure 1] 1A is an external perspective view of one embodiment of a resin molded product according to the present invention, where A shows one embodiment, B shows another embodiment, C shows another embodiment, and D shows still another embodiment. [Diagram 2]1 is a schematic cross-sectional view of one embodiment of a mold according to the present invention. [Diagram 3] FIG. 1 is a partial external perspective view of one embodiment of a mold according to the present invention, where A shows one embodiment, B shows another embodiment, C shows another embodiment, and D shows still another embodiment. [Figure 4] 1A and 1B are a partial schematic cross-sectional view and a partial schematic perspective view of one embodiment of a mold according to the present invention. [Diagram 5] 4A and 4B are a partial schematic sectional view and a partial schematic perspective view, respectively, of one embodiment of a mold according to the present invention. [Figure 6] 1 is an explanatory diagram of a manufacturing method of a mold according to the present invention. [Figure 7] FIG. 4 is a schematic cross-sectional view of another embodiment of a mold according to the present invention. [Figure 8] FIG. 11 is a schematic cross-sectional view of still another embodiment of a mold according to the present invention. [Figure 9] FIG. 4 is a schematic cross-sectional view of another embodiment of a mold according to the present invention. [Figure 10] FIG. 11 is a schematic cross-sectional view of yet another embodiment of a mold according to the present invention. [Figure 11] FIG. 11 is a schematic cross-sectional view of still another embodiment of a mold according to the present invention. [Figure 12] FIG. 2 is a perspective view of an embodiment of a mold according to the present invention. [Figure 13] FIG. 2 is a perspective view of an embodiment of a mold according to the present invention, and is an explanatory view showing parts of the mold. [Figure 14] FIG. 1 is a perspective view of a resin molded product according to an embodiment of the present invention. [Figure 15] FIG. 2 is an explanatory diagram showing the contents of an antibacterial property evaluation test carried out using a resin molded product according to an embodiment of the present invention and a normal resin molded product. [Figure 16] 1 is a graph showing the results of an antibacterial evaluation test carried out using resin molded articles according to examples of the present invention and a normal resin molded article. [Figure 17] FIG. 2 is an explanatory diagram showing the results of a water repellency evaluation performed using a resin molded article having a microstructure according to an embodiment of the present invention and a normal resin molded article. [Figure 18]FIG. 1 is an explanatory diagram showing the results of a comparison of the transferability of a fine structure to a molded product with and without gas permeability, using an injection molding die. [Figure 19] 19 shows CT scan images of a mold according to an embodiment of the present invention. Figure 19(a) shows a 3D image, Figure 19(b) shows a 3D transmission image, Figure 19(c) shows a horizontal cross-sectional image of each layer, and Figure 19(d) shows a vertical cross-sectional image of each layer. [Figure 20] FIG. 2A is an explanatory side view and FIG. 2B is an explanatory oblique view of a gas permeation measurement test piece for conducting a gas permeation measurement test of a mold according to an embodiment of the invention. [Figure 21] FIG. 2 is an explanatory diagram of a gas permeation measuring device used in a gas permeation measuring test. [Figure 22] FIG. 1 is an explanatory diagram of gas permeation measurement test results. [Figure 23] This is a graph showing published test results of antibacterial evaluation of nanostructures created on silicon substrates, showing the viable bacteria rate versus pillar height. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] A resin molded product molded by a mold according to an embodiment of the present invention will be described below with reference to the drawings. 1, the resin molded product 1 is a resin molded product having fine protrusions 2 on its surface, the protrusions 2 having a height of 500 nm to 1000 nm and a pitch of 500 nm to 800 nm, where the pitch is the distance between the centers of adjacent protrusions 2.
[0022] Next, a method for manufacturing the above-mentioned resin molded product 1 will be described with reference to the drawings. The manufacturing method of the resin molded product of this embodiment uses a mold 3 shown in Fig. 2. The mold 3 is laminated on a base (not shown) and includes a truss layer 5 having gas flow passages 4 formed therein, a porous layer 6 laminated on the truss layer 5, a lattice layer 7 having a lattice-like structure laminated on the porous layer 6, and a gas-permeable mold surface layer 8 laminated on the lattice layer 7. The gas flow passages 4 are formed in an oblique manner as a result of the truss layer 5 having an internal structure in which triangular layers are stacked.
[0023] As shown in Fig. 3, recesses 9 are formed in a gas permeable mold surface layer 8. The size of the recesses 9 can be set as necessary, with a depth of 500 nm to 1000 nm and a pitch of 500 nm to 800 nm. Here, the pitch is the distance between the centers of adjacent recesses 9. In the manufacturing method of the resin molded product 1, a resin is injected into a cavity formed by the mold 3 and then hardened.
[0024] As shown in FIGS. 4 and 5, a mold 3 according to an embodiment of the present invention has a gas permeable functionally graded portion 10 formed by laminating a porous layer 6 and a lattice layer 7 on a truss layer 5 . The truss layer 5, the porous layer 6, and the lattice layer 7 are made of sintered metal, and the functions of each part are realized by adjusting the sintering temperature and time. Furthermore, the sintering is carried out continuously from the truss layer 5 to the porous layer 6 and the lattice layer 7, and the joint boundary between the truss layer 5 and the porous layer 6 and the joint boundary between the porous layer 6 and the lattice layer 7 are made into continuous layers formed by continuous sintering.
[0025] The gas flow passages 4 formed in the truss layer 5 are formed in an X-shaped configuration with multiple paths intersecting, which allows for the flow of large volumes of gas while at the same time reducing the weight of the truss layer 5 while maintaining its strength. Moreover, the porous layer 6 laminated on the truss layer 5 has gas permeability due to its porosity itself. On the other hand, gas passages 11 having a width of 100 to 120 μm and a pitch of 2.0 to 3.0 mm are formed in the lattice layer 7. Here, the pitch is the center-to-center spacing of the gas transmission holes 11a. In this way, by laminating the porous layer 6 and the lattice layer 7 on the truss layer 5 to form the gas permeable functionally graded portion 10, it is possible to maintain strength while allowing gas to permeate.
[0026] As the material for the gas permeable mold surface layer 8 shown in FIG. 3 that is laminated on the gas permeable functionally graded portion 10, for example, the polymerizable compound disclosed in Japanese Patent No. 6703253 can be used. This polymerizable compound can form a cured product with high gas permeability. In addition, since it simultaneously satisfies mechanical properties such as elastic modulus and various properties required in imprint molding (for example, solvent resistance, low linear thermal expansion (or dimensional stability), transparency (light transmittance), etc.), it can be used as an imprint molding template with high gas permeability. Since such a template can transfer a pattern with high accuracy even when a transfer agent containing a volatile component with a relatively large molecular size is used in imprint molding, molding defects (transfer defects) can be reduced, and further, damage to the pattern or generation of foreign matter due to peeling can be suppressed, so the durability of the template is high. Furthermore, such a template can be formed by effectively utilizing biomass resources such as organic compounds derived from sugar, and the burden on the natural environment can be reduced.
[0027] Gas permeability is ensured by the gas permeable mold surface layer 8 having a large number of pores 8a. The size of the recesses 9 can be set as necessary within the range of a diameter of 20 to 500 nm, a depth of 500 to 1000 nm, and a center-to-center distance between adjacent recesses 9 of 500 to 800 nm.
[0028] As described above, the truss layer 5 of the mold 3, the gas permeable mold surface layer portion 8, and the gas permeable gradient functional portion 10 are all gas permeable, which makes it possible to exhaust gas within the cavity formed by the mold 3 during injection molding, and also greatly improves the transferability of the mold 3 surface shape to the molded article.
[0029] Next, one embodiment of the method for manufacturing a mold according to the present invention will be described. 6, the manufacturing method of the mold of this embodiment includes a step of adhering a gas permeable surface layer liquid 8b to a gas permeable functionally graded portion 10 formed by laminating a porous layer 6 and a lattice layer 7 on a truss layer 5. Next, a step of placing an original plate 12 with a fine nanostructure on the gas permeable surface layer liquid 8b adhered to the lattice layer 7 of the gas permeable functionally graded portion 10 is performed.
[0030] This original plate 12 with a fine nanostructure has fine protrusions 12a formed on its surface in advance, and these protrusions 12a on the surface have a diameter of 20 to 500 nm, a height of 500 to 1000 nm, and a center-to-center distance between adjacent protrusions of 500 to 800 nm.
[0031] Next, a photocuring reaction step is carried out in which the gas permeable surface layer liquid 8b on which the original plate 12 with the fine nanostructure is placed is irradiated with ultraviolet light. The photocuring reaction process consists of a first step of irradiation process in which ultraviolet (UV) rays are irradiated for 30 seconds using Hamaphoto LC8, and a second step of irradiation process in which ultraviolet (UV) rays are irradiated for 1 minute using a metal halide lamp. In the first irradiation step, preliminary irradiation is performed, and in the second irradiation step, main irradiation is performed. By dividing the process into two steps in this manner, sufficient photocuring can be achieved.
[0032] Next, by removing the original plate 12 with the fine nanostructure, a mold 3 can be obtained, which is equipped with a transparent mold surface layer 8 having recesses 9 to which fine protrusions 12a previously formed on the surface of the original plate 12 with the fine nanostructure are transferred.
[0033] The resins to be injection molded using the mold 3 are thermoplastic resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polybutylene-ethylene terephthalate (PBT-PET copolymer resin), polyether ether ketone (PEEK resin), polyphenylene sulfide (PPS), polyetherimide (PEI), 6 nylon (PA6), 6-6 nylon (PA66), 6T nylon (PA6T), polyphthalamide (PPA), polystyrene (PS), ABS resin (ABS), polyvinyl chloride resin (PVC), polyacetal (POM), liquid crystal polymer (LCP), polysulfone (PSU), polypropylene (PP), polycarbonate (PC), etc. These can be used alone or in combination. Also, thermosetting resins such as phenolic resin (PF), epoxy resin (EP), diallyl phthalate resin (PDAP), silicone resin (SI), polyimide resin (PI), melamine resin (MF), and urea resin (UF) are used. In order to improve heat resistance and dimensional stability, inorganic fillers such as carbon fiber, glass fiber, glass beads, and talc may be appropriately blended into these thermoplastic resins and thermosetting resins. Organic fillers such as cellulose nanofibers may also be appropriately blended.
[0034] Fig. 7 is a schematic cross-sectional view of another embodiment of the mold according to the present invention. The mold 3 of this embodiment has a two-layer structure in which a gas-permeable mold surface layer 8 is laminated on a porous layer 6. By forming such a two-layer structure, gas permeability can be improved. However, the resin injection pressure when using the mold 3 of this embodiment is set taking into consideration the strength obtained in this mode.
[0035] 8 is a schematic cross-sectional view of yet another embodiment of the mold according to the present invention. The mold 3 of this embodiment has a two-layer structure in which a gas-permeable mold surface layer 8 is laminated on a lattice layer 7. Such a two-layer structure can improve gas permeability. However, the resin injection pressure when using the mold 3 of this embodiment is set taking into account the strength obtained in this embodiment.
[0036] 9 is a schematic cross-sectional view of another embodiment of a mold according to the present invention. The mold 3 of this embodiment has a three-layer structure in which a porous layer 6 is laminated on a lattice layer 7, and a gas-permeable mold surface layer 8 is laminated on the porous layer 6. By forming such a three-layer structure, it is possible to improve gas permeability and strength. However, the resin injection pressure when using the mold 3 of this embodiment is set taking into consideration the strength obtained in this mode.
[0037] Fig. 10 is a schematic cross-sectional view of yet another embodiment of a mold according to the present invention. The mold 3 of this embodiment has a three-layer structure in which a lattice layer 7 is laminated on a porous layer 6, and a gas-permeable mold surface layer 8 is laminated on the lattice layer 7. By forming such a three-layer structure, it is possible to improve gas permeability and strength. However, the resin injection pressure when using the mold 3 of this embodiment is set taking into consideration the strength obtained in this mode.
[0038] Fig. 11 is a schematic cross-sectional view of yet another embodiment of the mold according to the present invention. The mold 3 of this embodiment has a four-layer structure in which a lattice layer 7 is laminated on a truss layer 5, a porous layer 6 is laminated on the lattice layer 7, and a gas-permeable mold surface layer 8 is laminated on the porous layer 6. By using such a four-layer structure, it is possible to improve strength while maintaining the necessary gas permeability. However, the resin injection pressure when using the mold 3 of this embodiment is set taking into consideration the strength obtained in this mode.
[0039] [Example] Fig. 12 is a perspective view of the mold 3 of the present invention described above. Also, in each of the parts ABCD of the mold 3 shown in Fig. 13, the recesses shown in Fig. 3 are formed to different depths in the range of 500 to 1000 nm. Fig. 14 is a perspective view of a resin molded product obtained by injection molding using the mold 3. In the part ABCD of the resin molded product, protrusions corresponding to the recesses in each of the parts ABCD of the mold 3 as shown in Fig. 1 are formed to different heights in the range of 500 to 1000 nm. [Antibacterial evaluation test] FIG. 15 shows the details of an antibacterial evaluation test carried out using a resin molded product obtained by molding using a mold according to an embodiment of the present invention using polypropylene (PP) and a normal resin molded product. The test method was based on the revised JIS standard, and the test bacteria liquid (bacteria (Escherichia coli)) was dropwise inoculated onto specimens (resin molded products molded using the mold of the embodiment of the present invention and ordinary resin molded products) and covered with a polyethylene film as an evaporation prevention film. The specimens were cultured for 24 hours at 37°C and 100% relative humidity. After that, the specimens were washed out immediately after inoculation and 24 hours after culture for the ordinary resin molded product test pieces, and after 24 hours of culture for the resin molded product test pieces of the embodiment of the present invention, and the viable bacteria count of the washed out liquid was measured to calculate the viable bacteria concentration of the specimens.
[0040] The results of the antibacterial evaluation test are shown in Figure 16. As shown in Figure 16, a 7% decrease in bacterial cell concentration was observed in the resin molded test piece molded using the mold of the embodiment of the present invention having a fine shape, compared to a normal resin molded test piece without a fine shape.
[0041] Fig. 17 shows the results of a water repellency evaluation performed using a resin molded product having a fine structure molded using a mold according to an embodiment of the present invention obtained using polypropylene (PP) and a normal resin molded product. As shown in the figure, the contact angle of the resin molded product having a fine structure molded using a mold according to an embodiment of the present invention is 20 degrees higher than that of the normal resin molded product. From these results, it can be seen that the resin molded product molded using the mold of the present invention having a fine nano surface structure has high water repellency, low wettability with water, and can inhibit the growth of mold.
[0042] Figure 18 shows the results of a comparison of the transferability of a microstructure to a molded product with and without gas permeability, using an injection molding die. As shown in the figure, a polypropylene (PP) molded product molded with a die having a convex surface structure with a microstructure height of 500 to 1000 nm and no gas permeability did not have a microstructure formed in the molded product, resulting in poor transfer, whereas a polypropylene (PP) molded product molded with a die having a concave surface structure with a microstructure depth of 500 to 1000 nm that was gas permeable formed a microstructure in the molded product and transfer was good.
[0043] Figure 19 shows photographs obtained by performing a CT scan on mold 3 of the embodiment. Figure 19(a) shows a 3D image, Figure 19(b) shows a 3D transmission image, Figure 19(c) shows a horizontal cross-sectional image of each layer, and Figure 19(d) shows a vertical cross-sectional image of each layer. As shown in the figure, at the joint boundary between the truss layer 5 and the porous layer 6 and at the joint boundary between the porous layer 6 and the lattice layer 7, each layer is continuously and firmly joined.
[0044] FIG. 20 shows a gas permeation measurement test piece 13 for carrying out a gas permeation measurement test. The gas permeability measurement test piece 13 is formed by laminating a porous layer 6 on a lattice layer 7, and has a variable thickness of 1.0, 2.0, 3.0, 5.0, or 7.0 mm, and has a gas non-permeable portion 13a of 40φ and a gas permeable portion 13b of 20φ.
[0045] FIG. 21 shows a gas permeation measuring device 14 used in a gas permeation measuring test performed using the gas permeation measuring specimen 13. The gas permeation measurement device 14 has a jig (lower) 15 and a jig (upper) 16, and the gas permeation measurement test piece 13 is placed between the jig (lower) 15 and the jig (upper) 16. A pressure sensor (No. 2) 17 and a pressure sensor (No. 1) 18 are disposed near the jig (lower) 15 and the jig (upper) 16. The pressure sensor (No. 2) 17 detects the pressure inside the jig (upper) 16, and the pressure sensor (No. 1) 18 detects the pressure inside the jig (lower) 15. On the other hand, a flow meter (No. 1) 22 is connected to a compressor 20 via a regulator 21 in a gas flow upstream side pipe 19 of the jig (lower part) 15 so as to be capable of passing gas. Further, a flow meter (No. 2) 24 is disposed in the piping 23 on the downstream side of the gas flow of the jig (upper part) 16 .
[0046] FIG. 22 shows the results of a gas permeation measurement test carried out using a gas permeation measurement specimen 13 and a gas permeation measurement device 14. As shown in the figure, a gas permeation measurement test performed using a 1.0 mm thick gas permeation measurement test piece 13 showed effective gas permeability at 0.2 to 0.3 MPa, and a gas permeation measurement test performed using a 2.0 mm thick gas permeation measurement test piece 13 showed effective gas permeability at 0.4 to 0.7 MPa. [Explanation of symbols]
[0047] Reference Signs List 1 resin molded product, 2 convex portion, 3 mold, 4 gas flow passage, 5 base, 6 porous layer, 7 lattice layer, 8 gas permeable mold surface layer, 9 concave portion, 10 gas permeable functionally graded portion, 11 gas passage, 12 original plate with fine nanostructure.
Claims
1. A mold comprising: a gas permeable sintered metal layer and a gas permeable mold surface layer laminated on the gas permeable sintered metal layer.
2. 2. The mold according to claim 1, wherein the gas permeable sintered metal layer comprises at least one of a gas permeable truss layer, a gas permeable porous layer, and a gas permeable lattice layer.
3. 3. The mold of claim 2, wherein at least two of the gas permeable truss layer, the gas permeable porous layer and the gas permeable lattice layer are continuous sintered layers.
4. 2. The mold according to claim 1, wherein a recess having a depth of 500 to 1000 nm is formed in the surface layer of the gas permeable mold.
5. 5. The mold according to claim 4, wherein the center-to-center distance between adjacent recesses is 500 to 800 nm.
6. A method for manufacturing a mold, comprising the steps of: forming at least two of a gas permeable truss layer, a gas permeable porous layer, and a gas permeable lattice layer by continuous sintering; adhering a gas permeable surface layer liquid to one of the gas permeable truss layer, the gas permeable porous layer, and the gas permeable lattice layer; placing an original plate with a fine nanostructure on the gas permeable surface layer liquid adhered to the lattice layer; a photocuring reaction step of irradiating ultraviolet light to the gas permeable surface layer liquid on which the original plate with a fine nanostructure is placed; and removing the original plate with a fine nanostructure.
7. The method for manufacturing a mold according to claim 6, wherein the original plate with a fine nanostructure has fine projections formed on its surface, the projections on the surface having a height of 500 to 1000 nm.
8. The method for manufacturing a mold according to claim 7, wherein the center-to-center distance between adjacent convex portions is 500 to 800 nm.
Citation Information
Patent Citations
Blower fan and its coating method
JP2008292069A
Air conditioner
JP2010019498A
Cited By
Imprint molding template, mold, and method for manufacturing mold
WO2025216257A1